Report on the 8th European Congress on Menopause. (September 2009) - Eglinton, Elizabeth; Al-Azzawi, Farook
The 8th European Congress on Menopause (EMAS), held 16–19 May 2009 in London, UK, was organized by the European Menopause and Andropause Society and hosted by the British Menopause Society (BMS). The Congress invited speakers from a range of European countries as well as some from the USA, Ecuador, Chile, Australia and South Africa, and attracted 1470 participants from over 70 countries as far a field as the Americas and East Asia.